Comparative analysis of condition and convection drying of paddy in a rotary dryer - Sahu, Mahesh Kumar; Illangantileke, Sarath G.; Athapol Noomhorm; Jindal, Vinod Kumar; Waibel, Hermann; Royal Government of The Netherlands (Bangkok : Asian Institute of Technology, 1989)
The performance of an axial flight prototype rotary dryer using heated air for driving paddy was investigated. Drying air temperature in the range of 60 to 100 ·c was used for paddy having initial moisture content in the range of 18 to 24% w. b. A two stage paddy drying operation was found suitable to minimise the reduction in head yield with provision of tempering inbetween the drying stages. Paddy could be dried to about 14% w.b . and. the driving characteristics could be well represented by simple logarithmic model. For comparison paddy was dried using conduction heating . Also a combination drying consisting of first stage conduction heating and second stage heated air drying was tried. The moisture canoe used was same in all the systems but the temperature used was different in conduction heating depending on the optimum conditions found from the earlier studies on conduction drying to paddy. The milling quality was found to be same in all the systems. The drying efficiency was higher in heated air drying than in conduction heating. The energy efficiency was almost same in all the systems . Cost comparison showed t h at conduction drying incurred minimum operating cost per ton of paddy followed by combination drying. Heated air drying incurred maximum cost.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Rice -- Drying